Men's nutrition knowledge is important for women's and children's nutrition in Ethiopia. Issue 1 (4th August 2020) - Ambikapathi, Ramya; Passarelli, Simone; Madzorera, Isabel; Canavan, Chelsey R.; Noor, Ramadhani A.; Abdelmenan, Semira; Tewahido, Dagmawit; Tadesse, Amare Worku; Sibanda, Lindiwe; Sibanda, Simbarashe; Munthali, Bertha; Madzivhandila, Tshilidzi; et al.
Abstract: In an effort to address undernutrition among women and children in rural areas of low‐income countries, nutrition‐sensitive agriculture (NSA) and behaviour change communication (BCC) projects heavily focus on women as an entry point to effect nutritional outcomes. There is limited evidence on the role of men's contribution in improving household diets. In this Agriculture to Nutrition trial (Clinicaltrials.gov identifier: NCT03152227), we explored associations between men's and women's nutritional knowledge on households', children's and women's dietary diversity. At the midline evaluation conducted in July 2017, FAO's nutrition knowledge questionnaire was administered to male and female partners in 1396 households. There was a high degree of agreement (88%) on knowledge about exclusive breastfeeding between parents; however, only 56–66% of the households had agreement when comparing knowledge of dietary sources of vitamin A or iron. Factor analysis of knowledge dimensions resulted in identifying two domains, namely, 'dietary' and 'vitamin' knowledge. Dietary knowledge had a larger effect on women's and children's dietary diversities than vitamin knowledge. Men's dietary knowledge had strong positive associations with households' dietary diversity scores (0.24, P value = 0.001), children's dietary diversity (0.19, P value = 0.008) and women's dietary diversity (0.18, P value < 0.001). Distance to markets and men's education levels modified the effects of nutrition knowledge on dietary diversity. While previous NSA and BCC interventions predominantly focused on uptake among women, there is a large gap and strong potential for men's engagement in improving household nutrition. Interventions that expand the role of men in NSA may synergistically improve household nutrition outcomes.